Social Issues in Management: Comments on the Past and Future. Issue 7 (September 2019) - Carroll, Archie B.
This essay comments on the past and the future of the Social Issues in Management (SIM) Division of the Academy of Management (AOM). The essay addresses the two major questions posed to the commentators on this special issue: First, does the past of the SIM Division provide any clues as to its future? Second, where is the SIM Division going or where should it be going? The author has been a member of SIM since 1971 and served as program chair in 1975 and division chair in 1976 to 1977. SIM is certainly a field at the community and administrative levels, and you could argue that SIM is a discipline, though we are interdisciplinary. It is not as certain that we are unique or distinctive at the intellectual level because we are not always that different in kind or quality from what is being done elsewhere in AOM, and there are more and more scholars in other divisions now working on topics that we once worked on exclusively. However, it is equally unlikely that many of the other AOM divisions could meet a test of intellectual uniqueness. The essay emphasizes some ideas that might help improve the intellectual rigor of the SIM meetings, and the value of alliances with Society for Business Ethics (SBE) and International Association for Business and Society (IABS). A division name change, even if desirable, is not a compelling issue.